Los preverbos en maya yucateco - Armstrong, Grant; AnderBois, Scott; Dzidz Yam, Edber (El Colegio de México, A.C., 2024)
In linguistic descriptions of Mayan languages there is often a class of adverbs that exhibit exceptional behavior called “dependent adverbs”, “incorporated adverbs” or “clitic adverbs”, among other names. Their most notable characteristic is that they appear between the verb root and the set A bound pronoun or aspect marker in the clause. The objective of this paper is to present an argument in favor of the idea that, in Yucatec Maya, this adverbial class should be treated as its own lexical category that we label preverbos, which is distinct from adverbs. We present morphological, syntactic and semantic evidence in favor of distinguishing preverbos from both adverbs and from incorporated roots in compound verbal stems. Finally, we provide a detailed semantic classification of preverbos and propose a syntactic analysis that explains their grammatical properties.